ANALISIS PENERAPAN SISTEM PENJADWALAN DENGAN METODE PERT PADA PROYEK KONSTRUKSI (STUDI KASUS: REHABILITASI DAN PENINGKATAN INFRASTRUKSI PASAR TRADISONAL KOTA MALANG) - Faris Rizal Andardi (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2020)
PERT is a simplified software, to produce the expected project completion probability based on the duration or duration of a particular contract. In developing the PERT method a lot of research was carried out to perfect this method. The purpose of this study is to determine the overall duration of project completion, the magnitude of the project probability that can be completed in less than 170 days and more than 170 days, and the project completion time with the highest probability. Results of Analysis of Implementation of Scheduling System with PERT Method in Rehabilitation and Improvement of Traditional Market Infrastructure Projects in Malang City is the total duration of simulation results obtained 168 days faster than the 172 day plan. The probability of completing the 168 day project is 50%, while the probability of completing the 172 day project is 85.31%. The highest chance of the project being completed is 99.97%, with a duration of 181 days.